Competition efficiency analysis of Croatian junior wrestlers in European Championship - Slacanac, K.; Baic, M.; Starcevic, N. (SportMont, 2016)
Croatian junior wrestler won a bronze medal at the European Championship 2016 year. Considering the potential of our wrestlers there is an obvious need of technical and tactical analysis so our juniors and seniors U23 wrestlers would be able to achieve even better results. Match analysis were conducted by LongoMatch 0.20.1. Seven matches of Croatian wrestlers were analysed. Time parameters, score efficiency, technical efficiency and tactical structure were observed and analysed from the aspect of attack and defence phase and successful/unsuccessful techniques. This paper shows descriptive parameters and competitor efficiency were calculated. The results show a great number of positive score in a standing position in relation to parterre position. The parameters of competitive efficiency (0.49 points per minute) show better attacking efficiency (1.32 points per minute) in relation to defence efficiency (0.83 points per minute). Croatian wrestlers achieve less score per minute in relation with elite wrestlers, but it is visible a significant progress in technical and tactical efficiency in relation in the past three year. According to place realization of technique, Croatian wrestlers realized more technique in the center, while opponents realized technique in the zone and moving to the zone. Further analysis of efficiency and individualisation training will improve efficiency of Croatian national wrestlers.